2018
DOI: 10.1002/app.46861
|View full text |Cite
|
Sign up to set email alerts
|

One‐pot synthesis of palm oil‐based polyester polyol for production of biodegradable and biocompatible polyurethane

Abstract: Palm oil-based polyester polyol was synthesized by reacting epoxidized palm olein with malonic acid under a convenient one-pot synthesis method. The optimum reaction time, temperature, and functionality molar ratio were determined. The optimal polyol consisted of hydroxyl and acid values of 98.19 and 1.44 mg KOH/g sample, 95% conversion of epoxides and M n of 5201 Da; and the chemical structure was elucidated by Fourier transform infrared , Carbon-13 nuclear magnetic resonance (NMR), and 1 H-NMR. The polyol wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…On the other hand, PU 1.0, PU 0.9 and PU 0.8, with lower water uptakes of 199–231%, were relatively stable; demonstrating a mass loss of 7.3%, 8.8% and 11.1%, respectively, for 28 days of incubation. A comparison was made with our previous report on the polyurethane prepared with malonic acid derived palm oil-based polyol [ 31 ], whereby the biodegradation rate of the present work has shown much improvement in terms of mass loss and water uptake. The previous work reported that the water uptake of the polyurethanes was only up to 145% and the maximum mass loss was 15.3% for 28 days of enzymatic incubation, when malonic acid was used as reactant in the palm oil-based polyol synthesis.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…On the other hand, PU 1.0, PU 0.9 and PU 0.8, with lower water uptakes of 199–231%, were relatively stable; demonstrating a mass loss of 7.3%, 8.8% and 11.1%, respectively, for 28 days of incubation. A comparison was made with our previous report on the polyurethane prepared with malonic acid derived palm oil-based polyol [ 31 ], whereby the biodegradation rate of the present work has shown much improvement in terms of mass loss and water uptake. The previous work reported that the water uptake of the polyurethanes was only up to 145% and the maximum mass loss was 15.3% for 28 days of enzymatic incubation, when malonic acid was used as reactant in the palm oil-based polyol synthesis.…”
Section: Resultsmentioning
confidence: 68%
“…In view of the versatility of the polyurethanes and their prospect in medical and biomedical applications, and considering the health, safety and environmental issues that most polyurethanes in the industries are produced by the carcinogenic aromatic isocyanates and polyols from non-renewable feedstocks, we reported on the synthesis of a PPP by reacting epoxidized palm oil with malonic acid in a convenient one-pot synthesis method [ 31 ]. The previous work focused on the synthesis and optimization of the production of PPP using malonic acid, whereby the effect of reaction temperature, reaction time and functionality molar ratios (epoxy: carboxyl) of EPO and malonic acid on the physico-chemical properties of the polyols were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, PEG-HMDI based TPU scaffolds had a low stiffness (257–1781 kPa), while biodegradation behavior was not characterized . There are several other reports in the literature which stated lower stiffness values for TPU scaffolds compared to the ones synthesized in this study; however in these, the biodegradation profiles were either not characterized or they exhibited very rapid degradation, which is not suitable with the regeneration rate of the native skeletal muscle tissue. Various others used TPU scaffolds with a much higher Young’s modulus than the polymers synthesized in this study. ,, Furthermore, an important feature of TPUs is their high stretchability while maintaining their shape (elasticity) before breaking. As can be seen in Table , while PCL elongates only 28% at break, highly flexible TPU-3 stretches about 900%.…”
Section: Discussionmentioning
confidence: 67%
“…Yeoh and coworkers used 100% palm oil-based polyester polyol without incorporating petrochemical-based polyol to prepare exible porous PUs. 61 They used aliphatic diisocyanate, i.e., IPDI, since the degradation products of IPDIbased PUs showed lower toxicity than those from the degradation products of aromatic diisocyanate-based PUs. 89 The obtained PU had a density of 95-122 kg m −3 , high porosity (89-90%), 35-2165 mm pore sizes (interconnected micro and macropore), compression stress of 48-55 kPa, and 59-78 kPa tensile strength.…”
Section: Polyurethanes (Pus)mentioning
confidence: 99%